Les Représentations Schématiques Des Enseignants Stagiaires En Sciences De La Vie Et De La Terre : Quelles Compétences Pour Une Utilisation Pédagogique? - El Hnot, Hasnae; Cherai, Bouamama; Sibari, Hayat (European Scientific Journal, ESJ, 2017)
This article aims to analyze schemes made by teacher trainees in Life and Earth sciences at the Regional Center of the Trades of Education and Training (CRMEF) Tangier-Tetouan-Al Houceima- middle school - in order to identify the conceptions of these future teachers about the schematic representation of a concept. An analysis was made of 30 teacher trainees diagrams at the beginning of their qualifying training on concepts in internal geodynamics. The results obtained have shown that they are generally known by teacher trainees, but their schematic representations raise many problems, notably the scientific aspect of the scheme, the maintenance of a correct methodological organization and the respect for the symbolic code to be done on a scientific basis. To remedy this, the qualifying training of these teacher trainees must be reinforced with schematization sessions supplemented by an integration of these schemes in sequences of learning for better pedagogical use.